Phage ϕC2 Mediates Transduction of Tn6215, Encoding Erythromycin Resistance, between Clostridium difficile Strains - Shan Goh (American Society for Microbiology, 2013)
ABSTRACT In this work, we show that Clostridium difficile phage ϕC2 transduces erm(B), which confers erythromycin resistance, from a donor to a recipient strain at a frequency of 10−6 per PFU. The transductants were lysogenic for ϕC2 and contained the erm(B) gene in a novel transposon, Tn6215. This element is 13,008 bp in length and contains 17 putative open reading frames (ORFs). It could also be transferred at a lower frequency by filter mating. IMPORTANCE Clostridium difficile is a major human pathogen that causes diarrhea that can be persistent and difficult to resolve using antibiotics. C. difficile is potentially zoonotic and has been detected in animals, food, and environmental samples. C. difficile genomes contain large portions of horizontally acquired genetic elements. The conjugative elements have been reasonably well studied, but transduction has not yet been demonstrated. Here, we show for the first time transduction as a mechanism for the transfer of a novel genetic element in C. difficile. Transduction may also be a useful tool for the genetic manipulation of C. difficile.